Shock deformation confirms the impact origin for the Cerro do Jarau, Rio Grande do Sul, Brazil, structure - Reimold, Wolf Uwe; Crosta, Alvaro Penteado; Hasch, Maximilian; Kowitz, Astrid; Hauser, Natalia; Sanchez, Joana Paula; Amarante Simoes, Luiz Sergio [UNESP]; Oliveira, Grace Juliana de; Zaag, Patrice T. (Wiley-Blackwell, 2019)
Cerro do Jarau is a conspicuous, circular morpho-structural feature in Rio Grande do Sul State (Brazil), with a central elevated core in the otherwise flat Pampas terrain typical for the border regions between Brazil and Uruguay. The structure has a diameter of approximately 13.5 km. It is centered at 30(o)12 ' S and 56(o)32 ' W and was formed on basaltic flows of the Cretaceous Serra Geral Formation, which is part of the Parana-Etendeka Large Igneous Province (LIP), and in sandstones of the Botucatu and Guara formations. The structure was first spotted on aerial photographs in the 1960s. Ever since, its origin has been debated, sometimes in terms of an endogenous (igneous) origin, sometimes as the result of an exogenous (meteorite impact) event. In recent years, a number of studies have been conducted in order to investigate its nature and origin. Although the results have indicated a possible impact origin, no conclusive evidence could be produced. The interpretation of an impact origin was mostly based on the morphological characteristics of the structure; geophysical data; as well as the occurrence of different breccia types; extensive deformation/silicification of the rocks within the structure, in particular the sandstones; and also on the widespread occurrence of low-pressure deformation features, including some planar fractures (PFs). A detailed optical microscopic analysis of samples collected during a number of field campaigns since 2007 resulted in the disclosure of a large number of quartz grains from sandstone and monomict arenite breccia from the central part of the structure with PFs and feather features (FFs), as well as a number of quartz grains exhibiting planar deformation features (PDFs). While most of these latter grains only carry a single set of PDFs, we have observed several with two sets, and one grain with three sets of PDFs. Consequently, we here propose Cerro do Jarau as the seventh confirmed impact structure in Brazil. Cerro do Jarau, together with Vargeao Dome (Santa Catalina state) and Vista Alegre (Parana State), is one of very few impact structures on Earth formed in basaltic rocks.